Conservation officer perceptions of search authority. (2nd January 2022) - Rossler, Michael T.; Suttmoeller, Michael J.
ABSTRACT: To date, a great deal of confusion and misinformation surrounds the authority (and therefore potentially wider discretion) that conservation officers possess to search private property, vehicles, and residences. Utilizing a survey of approximately 1, 600 officers employed in 15 state-level conservation agencies in the United States, the current inquiry examines conservation officer perceptions of their search authority. Findings indicate there is substantial state-level variation in statutory authority granted to conservation officers relative to their search and seizure capabilities. A substantial percentage of conservation officers believe that they possess authority to search private property beyond that granted to other law enforcement officers. Findings indicate that this perception is less common for vehicles or private residences. The findings from this study have implications for conservation officer training, policy, and procedure.